Evolutionary insights inferred by molecular analysis of the ITS1-5.8S-ITS2 and IGS Avena sp. sequences - Nikoloudakis, Nikolaos; Skaracis, George N.; Katsiotis, Andreas (My University, 2008)
In an attempt to clarify phylogenetic and genome relationships among 35 diploid (A and C genomes), 13 tetraploid (AB and AC genomes) and 6 hexaploid (ACD genome) Avena taxa, 71 clones of the ITS1-5.8S-ITS2 fragment were sequenced, aligned and a network was constructed. In addition, the intergenic spacer (IGS) fragment was fingerprinted by means of a RFLP analysis using three different restriction enzymes. Both approaches led to comparable results. Clustering among the 54 Avena sp. entries was according to karyotype. Major genic divergence between the A and C genomes was revealed, while distinction among the A and B/D genomes was not possible. High affinity among the AB genome tetraploids and the A(s) genome diploid A. lusitanica was found, while AC genome tetraploids and ACD hexaploids were highly affiliated with the A(l) genome diploid A. longiglumis. The possible role of A. longiglumis in Avena sp. evolution is discussed.
Keywords: Avena; Evolution; Intergenic spacer; Internal transcribed spacer; Network; Phylogeny; rDNA